Observation of mating behaviour in Phayre’s Langur (Trachypithecus phayrei) in Lawachara National Park, Bangladesh - Sattar, Auritro; Nath, Shimul; Mithu, Atikul Islam (Bangladesh Journal of Zoology, 2025)
Abstract not Available Bangladesh J. Zool. 53(1): 125-129, 2025